Effects of diluents on cycle-by-cycle variations in a spark ignition engine fueled with methanol. (1st September 2019) - Zhang, Miaomiao; Hong, Wei; Xie, Fangxi; Liu, Yu; Su, Yan; Li, Xiaoping; Liu, Haifeng; Fang, Kangning; Zhu, Xinbo
Abstract: Effects of three diluents on cycle-by-cycle variations of a spark ignition engine fueled with methanol were studied in this paper. Peak in-cylinder pressure, maximum rate of pressure rise and indicated mean effective pressure were investigated experimentally to assess these influences. The results showed that when addition ratios of carbon dioxide and nitrogen increased, the fluctuations of peak pressure and maximum rate of pressure rise increased first and then decrease, the dispersion of indicated mean effective pressure was enlarged, the mean values of these parameters all decreased gradually while carbon dioxide dropped faster. These three parameters did not present clear changes in fluctuation for Argon, only that their mean values showed a slight difference. Linearities between peak pressure and maximum rate of pressure rise corresponding to their crank angles were observed at low addition ratio of carbon dioxide and nitrogen, while it would disappear if the mixture was further diluted. Cycle-by-cycle variations of tested engine would be deteriorated by carbon dioxide and nitrogen, while it kept unchanged and indicated mean effective pressure was increased for argon dilution. The diluent tolerance of this methanol engine is higher than that of gasoline engine. Highlights: Cycle-by-cycle variations of a spark ignition methanol engine were examined. Carbon dioxide dilution deteriorates methanol engine's cyclic variations mostly. Argon dilution enhances Indicated mean effective pressure of methanol engine. Cyclic variations of methanol engine changed slightly with argon dilution. Methanol engine's diluent tolerance is higher than gasoline direct injection engine.